THE IMPACT OF LIPID PEROXIDATION’S STATE ON EFFECTIVENESS OF BREAST CANCER NEOADJUVANT INTRA-ARTERIAL POLYCHEMOTHERAPY - Sedakov, I.E.; Yakubenko, E.D.; Zinkovych, I.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
On the basis of 5-years observation of 84 advanced breast cancer cases was shown that the diseaseprogression was more rarely in the patients were appeared the reduction of lipid peroxidation rate and declined in the serum.-tocopherol level in response to intra-arterial chemotherapy course. Such patterns werenot registered for antioxidant enzymes.